2018
DOI: 10.3233/bme-181732
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-structure interaction of patient-specific Circle of Willis with aneurysm: Investigation of hemodynamic parameters

Abstract: This study showed that the distribution of parameters was dependent on the geometry of the COW, and maximum values are seen in areas prone to aneurysm formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…After evaluation of the titles and abstracts, 70 articles were selected for full-text assessment. Three studies met the inclusion criteria for this review [ 26 , 27 , 28 ]. The most frequent reason for exclusion ( n = 30) was that adapted boundary conditions were not personalized.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After evaluation of the titles and abstracts, 70 articles were selected for full-text assessment. Three studies met the inclusion criteria for this review [ 26 , 27 , 28 ]. The most frequent reason for exclusion ( n = 30) was that adapted boundary conditions were not personalized.…”
Section: Resultsmentioning
confidence: 99%
“…Jahed et al segmented CoW and IA from CTA images [ 28 ]. Patient-specific pulsatile velocity profiles of inlets and outlets were obtained from Transcranial Doppler (TCD).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recanalization after coiling is related to aneurysmal growth to greater or lesser degrees (3435). Several experimental studies using computational fluid dynamics in a patient-specific vascular model have further indicated that the elasticity of the vascular wall may play a fundamental role in deformation of the arterial wall (363738). A rigid (vs. elastic) wall serves to increase wall shear stress acting on the vascular wall in a pulsatile flow, potentially accentuating the hemodynamic impact on the endothelial cell, intima, and smooth muscle cell.…”
Section: Discussionmentioning
confidence: 99%
“…The FSI models could simulate the blood flow in CoW [70] and its fluctuations under cervical rotator manipulation [71]. With in-vivo measurement of blood flow velocity by transcranial Doppler as inlet condition, capillary blood pressure as outlet condition, and age-related elastic modulus of arterial wall, Jahed et al investigated the effects of different hemodynamic and mechanical parameters (wall shear stress, blood pressure, mechanical stress, displacement) on the formation of aneurysms [72]. They found strong effects of these parameters on the size of aneurysm and the risk of aneurysm rupture at arterial bifurcations or the neck of aneurysm.…”
Section: Clinical Applicationsmentioning
confidence: 99%